Peran Kepuasan Kerja Dalam Memoderasi Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, Dan Disiplin Kerja Terhadap Kinerja Aparatur Sipil Negara - Manfred Hae; Armanu Thoyib; Nasharuddin Mas; Choirul Anam; Emma Budi Sulistiarini; Adya Hermawati (Journal of Innovation Research and Knowledge, 2026)
This study aims to analyze the effects of transformational leadership, work culture, and work discipline on the performance of State Civil Apparatus (ASN), with job satisfaction as a moderating variable in the Maybrat Regency Government. The study employed a quantitative approach with an explanatory research design. The study population consisted of 237 ASN, while the sample comprised 70 respondents selected using proportionate stratified random sampling. Data were collected through questionnaires using a five-point Likert scale. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results showed that transformational leadership, work culture, work discipline, and job satisfaction had positive and significant effects on ASN performance. Furthermore, job satisfaction was found to strengthen the effects of transformational leadership and work discipline on ASN performance. However, job satisfaction did not moderate the effect of work culture on ASN performance. The findings indicate that improving leadership quality, strengthening work culture, implementing work discipline, and enhancing job satisfaction contribute to improved ASN performance. This study provides empirical contributions to the development of public-sector human resource management research, particularly regarding the role of job satisfaction as a moderating variable in the relationship between organizational factors and ASN performance within local government institutions